Multilocus phylogeny of Crenicichla (Teleostei: Cichlidae), with biogeography of the C. lacustris group: species flocks as a model for sympatric speciation in rivers - Piálek, Lubomír; Ríčan, Oldřich; Casciotta, Jorge; Almirón, Adriana; Zrzavý, Jan (Molecular phylogenetics and evolution, 2012)
First multilocus analysis of the largest Neotropical cichlid genus Crenicichla combining mitochondrial (cytb, ND2, 16S) and nuclear (S7 intron 1) genes and comprising 602 sequences of 169 specimens yields a robust phylogenetic hypothesis. The best marker in the combined analysis is the ND2 gene which contributes throughout the whole range of hierarchical levels in the tree and shows weak effects of saturation at the 3rd codon position. The 16S locus exerts almost no influence on the inferred phylogeny. The nuclear S7 intron 1 resolves mainly deeper nodes. Crenicichla is split into two main clades: (1) Teleocichla, the Crenicichla wallacii group, and the Crenicichla lugubris-Crenicichla saxatilis groups ("the TWLuS clade"); (2) the Crenicichla reticulata group and the Crenicichla lacustris group-Crenicichla macrophthalma ("the RMLa clade"). Our study confirms the monophyly of the C. lacustris species group with very high support. The biogeographic reconstruction of the C. lacustris group using dispersal-vicariance analysis underlines the importance of ancient barriers between the middle and upper Paraná River (the Guaíra Falls) and between the middle and upper Uruguay River (the Moconá Falls). Our phylogeny recovers two endemic species flocks within the C. lacustris group, the Crenicichla missioneira species flock and the herein discovered Crenicichla mandelburgeri species flock from the Uruguay and Paraná/Iguazú Rivers, respectively. We discuss putative sympatric diversification of trophic traits (morphology of jaws and lips, dentition) and propose these species flocks as models for studying sympatric speciation in complex riverine systems. The possible role of hybridization as a mechanism of speciation is mentioned with a recorded example (Crenicichla scottii).
Keywords: Animals; Phylogeography; cichlidy; Genetic Speciation; RNA, Ribosomal, 16S; Uruguay; Bayesova věta; pravděpodobnostní funkce; Bayes Theorem; multilokusová sekvenční typizace; rybí proteiny; Genetic Variation; Likelihood Functions; Phylogeny; Cichlids; Paraguay; Sequence Alignment; fylogeografie; Fish Proteins; sympatrie; Sympatry; vznik druhů (genetika); Multilocus Sequence Typing; zvířata; fylogeneze; genetická variace; RNA ribozomální 16S; sekvenční seřazení